Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Pre Operasi pada Pasien Sectio Caesarea dengan Tindakan Spinal Anestesi - Annisah Sugiarti; Danang Tri Yudono; Jerau, Emiliani Elsi (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Patients who are going to undergo surgery often experience anxiety, and the inability to overcome this anxiety can lead to pathological behavior and psychological reactions. Anxiety that is not handled properly can result in longer recovery times, increased postoperative pain, and decreased immunity to infection. This study aims to assess the relationship between family support and preoperative anxiety levels in caesarean section patients undergoing spinal anesthesia at RSUD dr. Soedirman Kebumen. The method used is a quantitative approach with a cross-sectional design. The study sample consisted of 95 respondents of elective pre-operative caesarean section patients using measuring instruments in the form of the APAIS questionnaire and family support questionnaires. The results showed that there was no significant relationship between family support and preoperative anxiety levels in caesarean section patients with spinal anesthesia, with a p-value of 0.859> 0.05 and a correlation coefficient of -0.019, so it can be concluded that family support does not affect the level of anxiety in preoperative caesarean section patients.